If y=e^(msin-1x),show that (1-x^2)d^y/dx^2 -xdy/dx -m^y = 0
  Thumbs up will be given

Dear Student ,
Please find below the solution to the asked query :

y=em sin-1xDifferentiating wrt x dydx=em sin-1x d m sin-1xdxdydx=em sin-1x m1-x2dydx=y m1-x2Squaring on both sides , we getdydx2=m2y21-x21-x2 dydx2=m2y2Differentiating again wrt x both sides , we get-2x dydx2+1-x2 2 dydxd2ydx2=2m2y dydx1-x2 d2ydx2-x dydx=m2y1-x2 d2ydx2-x dydx-m2y=0
Hope this information will clear your doubts about the topic .
If you have any more doubts just ask here on the forum and our experts will try to help you out as soon as possible .


  • 26
sorry its (m^2)y in the end
  • -2
What are you looking for?